Comparing the effect of blogging as well as pen-and-paper on the essay writing performance of Iranian graduate students. - Kashani, Hajar; Mahmud, Rosnaini; Kalajahi, Seyed Ali Rezvani (Canadian Center of Science and Education, 2013)
In today's world, there are lots of methods in language teaching in general and teaching writing in particular. Using two different tools in writing essays and conducting a study to compare the effectiveness of these two tools namely blog and pen-and-paper was the basis of this study. This study used a quantitative true experimental design aimed at comparing the students' writing performance scores by using pen-and-paper essay writing and blogging among Iranian graduate students of University Putra Malaysia (UPM). The result of this study showed that the tools by themselves could not effect on the quality of writing essays and improvement in the students' writing performance. However, using technology and in this study, Internet can motivate the EFL learners to write more eagerly since they may like innovation in learning in contrast with traditional old methods of learning writing and practicing it. Yet it does not necessarily improve their writing performance only because of using computer and Internet. The Iranian graduate students of UPM found blog more interesting and motivating tool for writing, but it was not as easy using as pen-and-paper for them with which everyone is familiar. This research could find answers to the research questions posed at the beginning of the study and investigated the hypotheses presented then.